The effect of vibration on active and passive range of motion in elite female synchronized swimmers - Sands, W. A.; McNeal, J. R.; Stone, M. H.; Kimmel, W. L.; Haff, G. G.; Jemni, M. (European Journal of Sport Science, 2008)
The purpose of this study was to assess the acute effects of vibration and stretching on passive and active forward split range of motion in elite adult female synchronized swimmers. Eleven athletes performed a passive forward split test measuring the height of the anterior superior iliac spine on both sides and an active split test on both sides by adopting an inverted split position. Then athletes were assigned randomly by right or left leg to receive vibration on one leg while stretching. The contralateral leg was stretched but did not receive vibration and served as the control. The treatment involved a 40-s exposure to vibration of the forward leg in a split and 40 s of vibration to the rear leg in a split. The athletes were then post-tested using the same protocols. The results indicated that the vibration had a statistically significant influence on passive forward split flexibility, but not active split flexibility. The results of this study confirm earlier work and further demonstrate the efficacy of vibration in enhancing range of motion in a passive split position. Given that it is often difficult to achieve large changes in range of motion with already highly trained elite athletes, this methodology shows considerable promise. Vibration may not be powerful enough to evoke changes in active range of motion in spite of the changes in passive range of motion.